Experiences in feeding and gastrointestinal dysfunction in children with CHARGE syndrome. Issue 11 (22nd September 2017) - Macdonald, Meghan; Hudson, Alexandra; Bladon, Angela; Ratcliffe, Elyanne; Blake, Kim
Abstract : Feeding issues are very common in individuals with CHARGE syndrome and can lead to increased morbidity and mortality. The aim of this study was to expand upon the limited knowledge base of feeding and gastrointestinal issues in individuals with CHARGE syndrome. Parents of individuals (age range 1–18 years) with CHARGE syndrome, with or without feeding/gastrointestinal issues, were recruited through international CHARGE syndrome associations and CHARGE syndrome Facebook pages. Parents completed three questionnaires: CHARGE diagnostic characteristics; Pediatric Assessment Scale for Severe Feeding Problems © and PedsQL™ Gastrointestinal Symptoms Scale; and open‐ended questions. Sixty‐nine completed questionnaires were included in the study analysis (median age 7; 58% females). Individuals who were completely tube fed ( n  = 21) had significantly more feeding difficulties than individuals who were either partially ( n  = 26) or completely orally fed ( n  = 20; p  < 0.001). Tube fed individuals also experienced more problematic gastrointestinal symptoms ( p  < 0.001). Constipation ( n  = 19, 30%), vomiting ( n  = 12, 19%), and choking ( n  = 11, 17%) were reported by parents as the greatest challenges. Problems exist throughout the entire gastrointestinal tract in many individuals with CHARGE syndrome. These issues are more common in individuals who receive nutrition completely through a feeding tube compared to individuals with at least partial oral feeding behaviors.